2018
DOI: 10.1039/c8rp00115d
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry topics posing incommensurate difficulty to students with low math aptitude scores

Abstract: The identification of students at risk for academic failure in undergraduate chemistry courses has been heavily addressed in the literature. Arguably one of the strongest and most well-supported predictors of undergraduate success in chemistry is the mathematics portion of the SAT (SAT-M), a college-entrance, standardized test administered by the College Board. While students scoring in the bottom quartile of the SAT-M (herein referred to as at-risk) perform significantly worse on first-semester chemistry asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 48 publications
2
68
0
Order By: Relevance
“…Structure and bonding, as well as spatial and symbolic representations, are important in both biology and chemistry, and thus may allow us to generalize our findings to courses in biology and organic chemistry (e.g., Graulich, 2015;Hoskinson et al, 2013). In addition, focusing on Lewis structure problems allowed us to eliminate the possible contribution of math skills in solving a problem, a factor that could occur in many general chemistry problems (e.g., Frey et al, 2017;Ralph and Lewis, 2018).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Structure and bonding, as well as spatial and symbolic representations, are important in both biology and chemistry, and thus may allow us to generalize our findings to courses in biology and organic chemistry (e.g., Graulich, 2015;Hoskinson et al, 2013). In addition, focusing on Lewis structure problems allowed us to eliminate the possible contribution of math skills in solving a problem, a factor that could occur in many general chemistry problems (e.g., Frey et al, 2017;Ralph and Lewis, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…In addition, focusing on Lewis structure problems allowed us to eliminate the possible contribution of math skills in solving a problem, a factor that could occur in many general chemistry problems (e.g., Frey et al. , 2017 ; Ralph and Lewis, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Students' difficulties with quantitative problem-solving have been attributed to difficulties with making sense of the conceptual knowledge embedded in the mathematical equations (Bing & Redish, 2007Schuchardt & Schunn, 2016;Tuminaro & Redish, 2007). In physics, chemistry, and biology, students struggle to apply mathematical equations they have learned in class to novel or more complex scenarios (Becker & Towns, 2012;Nakhleh, 1993;Ralph & Lewis, 2018;Schuchardt & Schunn, 2016;Stamovlasis et al, 2005). This difficulty has been attributed to students' tendency to apply memorized algorithmic procedures instead of making sense of connections between the mathematical equations and the modeled scientific phenomenon (Bing & Redish, 2009;Stewart, 1983;Taasoobshirazi & Glynn, 2009;Tuminaro & Redish, 2007).…”
Section: Scientists Use Mathematical Knowledge To Represent Ideas Abomentioning
confidence: 99%
“…However, studies on students solving quantitative problems show that they often solve problems by relying on algorithmic procedures without making connections between the mathematical equation and the scientific phenomenon (Bing & Redish, 2009;Stewart, 1983;Taasoobshirazi & Glynn, 2009;Tuminaro & Redish, 2007). This tendency to solve problems algorithmically has been associated with a failure to transfer problem-solving techniques to novel contexts or more complex problems (Becker & Towns, 2012;Nakhleh, 1993;Ralph & Lewis, 2018;Schuchardt & Schunn, 2016;Stamovlasis, Tsaparlis, Kamilatos, Papaoikonomou, & Zarotiadou, 2005). The reliance on algorithmic problem-solving strategies has been attributed to the different opportunities provided for sensemaking of mathematical equations in science during instruction (Bing & Redish, 2008;Lythcott, 1990;Schuchardt & Schunn, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In reality, learners are no longer fond of developing their vocabulary in the second language, and more so, in Science-related subjects. Likewise, Ralph and Lewis (2018) stated that poor mathematical skills increase the difficulty of Chemistry Incidentally, the researchers had observed that some learners tend to use their mobile phones during classroom discussion. It prompted him to develop a supplementary material that can assist the learners to easily access information at their own disposal.…”
Section: Part a Teachers' And Learners' Responses On The Causes Of Difficulties In Science Inquiry Skills Enrichmentmentioning
confidence: 99%